Uso de la creatinina como indicador de la excreción urinaria en bovinos Nellore - Posada, Sandra L; Noguera, Ricardo R; Rodríguez, Norberto M; Borges, Ana L (Revista Colombiana de Ciencias Pecuarias, 2012)
Summary The total collection of urine from grazing animals is a complex and difficult procedure, while in confined animal it requires the installation of funnels or urinary catheters that generate discomfort along with an increased risk of injury. Objective: the aim of this study was to validate the predictive ability of urine creatinine on urine output, in comparison with the total collection method. Urinary excretion is fundamental for the understanding of several variables related to ruminant nutrition. Methods: five Nelore animals were used. Animals were kept in confinement conditions and were offered feed and water ad libitum. The total volume of urine produced, determined by total collection in metabolic cages was compared with the estimated production calculated from creatinine excretion. Spot samples collected four hours after feeding the animals were analyzed for creatinine concentration during four experimental periods. Results: the statistical significance of paired t-test and the trend of the regression slope in the Bland-Altman analysis allow concluding that creatinine excretion, under our experimental conditions, was not an adequate predictor of urine volume. Conclusions: creatinine concentration in spot samples can be considered as the critical factor in this methodology due to the common diurnal variations of urine output and, therefore, the variations in the excretion of the metabolite. Key words: creatinine ratio, creatinine concentration, spot samples, urine volume. Resumen El conocimiento de la excreción urinaria es necesario para la determinación de diversas variables contempladas en la nutrición de rumiantes. Con animales en pastoreo, la recolección total de la orina representa un procedimiento complejo; y en confinamiento, demanda la instalación de embudos o sondas urinarias, que generan incomodidad y aumentan el riesgo de lesiones. Objetivo: el objetivo de este trabajo fue validar la capacidad de predicción de la producción urinaria a través de la excreción de creatinina, con respecto a la determinación realizada vía recolección total. Métodos: cinco cebuínos criados en régimen de confinamiento, recibiendo alimento y agua ad libitum, fueron empleados. La producción total de orina, determinada mediante recolección total en jaula metabólica, fue comparada con la producción estimada desde la excreción de creatinina. Muestras spot fueron recolectadas cuatro horas después de la alimentación y analizadas para concentración de creatinina durante cuatro fases experimentales. Resultados: la significancia estadística de la prueba t pareada y a la tendencia registrada por la pendiente de regresión en el análisis de Bland-Alt man, permiten concluir que la excreción de creatinina, bajo nuestras condiciones experimentales, no predijo adecuadamente el volumen urinario. Conclusiones: la concentración de creatinina en la muestra spot se considera el punto crítico de la metodología por las variaciones diurnas que se registran en la producción urinaria y, por tanto, en la excreción del metabolito. Palabras clave: coeficiente de creatinina, concentración de creatinina, muestras spot, volumen urinario. Resumo O conhecimento da excreção urinária é necessário para o estabelecimento de diversas variáveis listadas na nutrição de ruminantes. Com animais em pastejo, a coleta total de urina é um procedimento complexo, e em confinamento, requer a instalação de funis ou de cateteres urinários, o que gera desconforto e aumenta o risco de lesões. Objetivo: o objetivo deste estudo foi validar a capacidade preditiva da produção urinária através da excreção de creatinina, respeito a determinação feita por meio da coleta total. Métodos: cinco animais zebus criados em confinamento, recebendo alimento e água ad libitum, foram usados. A produção total de urina, medida pela coleta total em gaiolas metabólicas, foi comparada com a produção estimada desde a excreção de creatinina. Amostras spot foram coletadas quatro horas após alimentação e analisadas para concentração de creatinina durante quatro fases experimentais. Resultados: a significancia estatística da prova t pareada somada à tendência registrada pela pendente de regressão na análise de Bland-Altman, permitem concluir que a excreção de creatinina, sob nossas condições experimentais, não prediz adequadamente o volume urinário. Conclusões: a concentração de creatinina na amostra spot se considera o ponto crítico da metodologia pelas variações diurnas que se registram na produção urinaria e, portanto, na excreção do metabolito. Palavras chave: coeficiente de creatinina, concentração de creatinina, amostras spot, volume urinário.